Study of SiCl4/H2/O2 chemical kinetics and its application to fused silica glass synthesis. Issue 10 (3rd October 2018) - Huang, Yaosong; Lu, Zhen; Zheng, Lili
ABSTRACT: A comprehensive computational model is first presented, which is capable of describing multispecies turbulent reacting flow and particle formation and deposition. Then a detailed mechanism for SiCl4 /H2 /O2 reaction system is proposed and applied to the prediction of a counterflow laminar diffusion flame. Good agreement in flame temperature is obtained between numerical results and experimental data, and the augmented 30-reaction SiCl4 submechanism in the detailed mechanism has a significant impact on the SiO2 formation rate. To employ the detailed mechanism in three-dimensional simulations, the reduction of reaction mechanism is performed to eliminate inconsequential species and reactions. The physiochemical process in a silica glass furnace is first simulated with the detailed mechanism to obtain realistic sample compositions. Then, the directed relation graph (DRG) method is employed to construct three comprehensive skeletal mechanisms by considering all accessed compositions in the fused silica glass synthesis, and further analyzethe governing chemical kinetics. The predicted total SiO2 deposition on glass ingot is found to depend on mechanism reduction, and the species SiCl and HOCl are important for the formation of SiO2 and OH. While only two species and seven reactions are removed from the detailed mechanism even though the reduction threshold error of 0.15 has been employed. It is also found that the number of important chemical species and reactions is significant only in a narrow region, which indicates a great potential in local adaptive mechanism reduction. Therefore, the dynamic adaptive chemistry (DAC) is used to generate a small locally valid skeletal mechanism. For the same accuracy in temperature and SiO2 mass fraction, DAC method obtains higher speedup factor than that of DRG method.